Decoupling management inefficiency: Myopia, hyperopia and takeover likelihood - Tunyi Tunyi Abongeh (International Review of Financial Analysis, 2019)
Using combinations of accounting and stock market performance measures, we advance a comprehensive multidimensional framework for modelling management performance. This framework proposes “poor” management, “myopia”, “hyperopia” and “efficient” management, as four distinct attributes of performance. We show that these new attributes align with, and extend, existing frameworks for modelling management short-termism. We apply this framework to test the management inefficiency hypothesis using UK data over the period 1988 to 2017. We find that takeover likelihood increases with “poor” management and “myopia”, but declines with “hyperopia” and “efficient” management. Our results suggest that managers who focus on sustaining long-term shareholders' value, even at the expense of current profitability, are less likely to be disciplined through takeovers. By contrast, managers who pursue profitability at the expense of long-term shareholder value creation are more likely to face takeovers. Finally, we document the role of bidders as enforcers of market discipline.